Compassion Focused Therapy Groups: Evidence from Routine Clinical Practice. Issue 3 (2nd July 2018) - McManus, James; Tsivos, Zoe; Woodward, Sarah; Fraser, Janelle; Hartwell, Rosalyn
Abstract : Objectives: Psychological therapy groups for people in adult mental health services can relieve waiting list pressures and potentially reduce stigma and social isolation. Compassion-focused therapy (CFT) focuses on shame and self-criticism. The aim of this study was to evaluate a transdiagnostic CFT group. Design: Quantitative and qualitative data were obtained from 13 people who completed the group. Methods: Participants completed a range of pre- and post-group self-report outcome measures that assess self-criticism and self-compassion. Results: Statistically significant improvements were found on all measures used, suggesting that attending the CFT group did result in meaningful changes. People who completed the group also provided positive feedback about the experience. Conclusions: The results suggest that running CFT groups is feasible and acceptable to clients with a range of psychiatric diagnoses as part of their care from community mental health teams. People who completed the group demonstrated significant improvements. A proportion of people did not complete the group, and more research is required about the reasons for this. Limitations of this study are considered together with future directions for research into CFT.